Beyond panaceas: Assessing the implementation and performance of participatory, multi-level governance in european water resource management - Jager, Nicolas W. (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2016)
Water is an essential natural resource, yet we are experiencing a global water crisis. This crisis is first and foremost a crisis of governance rather than of actual physical resources. Capacities of single, unitary states are severely challenged by the complex, multi-scalar, and dynamic structure of contemporary problems in water resource management. New modes of governance stress the potential of public participation and scalar restructuring for effective and legitimate environmental decision-making. However, a lack evidence on the actual implementation and instrumental value of novel governance modes stands in stark contrast to the strong beliefs and assumptions that often see these being propagated as ´panaceas´ or ´universal remedies´. With this doctoral dissertation I aim to contribute to a deeper understanding of the implementation and performance of public participation and scalar restructuring in environmental governance, and particularly to engage in systematic research into the contextual factors that shape the performance of such governance innovations. Based on the conceptual approaches of participatory, multi-level governance and scale, I advance a conceptual framework specifying mechanisms and important contextual factors describing the potential of participation and rescaling to impact on the efficacy of environmental decision-making. Applying this framework, I employ a mixed-methods approach combining qualitative, quantitative, set-theoretic, and review methods, with the aim of maximising the validity of results. Drawing on the institutional frame of the European Water Framework Directive (WFD), I first assess the extent and conditions under which participation and rescaling are actually implemented in the European water resource management regime. Subsequent analyses examine whether these governance shifts, where implemented, actually lead to environmentally effective and legitimate political decisions, and foster social outcomes. Results indicate that actual changes in governance structures remain modest, whereas previous institutional structures and experiences prove rather durable. Hence, despite recent shifts distributing authority towards alternative actors and scales, the state has persisted in its role as central authority in the European water resource management regime. To the extent that they were implemented, public participation and rescaling were generally positively related with the environmental effectiveness and legitimacy of political outcomes. The analysis provides a context-sensitive understanding, by unravelling the supposedly linear relationship between governance inputs and outputs to develop a more nuanced picture of the governance process rather as a composition of multiple, interdependent causal mechanisms that, depending on their actual configuration, lead to various outcomes. In this way, particularly the tension between legitimacy and effectiveness of political outcomes is disentangled, with both being seen as the result of distinct but interrelated properties of the governance system and its contextual circumstances. The thesis furthermore provides insights of practical and policy relevance, highlighting the need and potential to take a context-sensitive perspective in policy design and decision-making. The framework paper and the Ph.D. thesis thus together enhance academic understanding of environmental governance and its potential contributions to sustainability transitions.

Trotz der essentiellen Bedeutung der Ressource Wasser erleben wir derzeit eine Krise von globalem Ausmaß. Diese Krise ist jedoch zuvorderst eine politische Krise und weniger eine der physischen Ressource selbst. Die Kapazitäten und Möglichkeiten etablierter einzelstaatlicher Strukturen werden durch die komplexe, multi-skalare und dynamische Struktur der Probleme im Wasserressourcenmanagement stark in Frage gestellt. Demgegenüber betonen alternative Modi der politischen Steuerung die Potenziale von Öffentlichkeitsbeteiligung und skalarer Umstrukturierung als Mittel zu einer effektiveren und legitimeren Umweltpolitik. Jedoch steht den starken Hoffnungen und Überzeugungen in den instrumentellen Wert dieser neuen Steuerungsmodi ein Mangel an empirischer Evidenz entgegen. Es ist daher das Ziel dieser Dissertation zu einem vertieften Verständnis der Umsetzung und Leistungsfähigkeit von partizipativer und skalar umstrukturierter Governance beizutragen. Besonderes Augenmerk gilt der systematischen Analyse von Kontextfaktoren und Bedingungen und deren Einfluss auf die Wirksamkeit von alternativen Modi politischer Steuerung. Die theoretische Grundlage dieser Arbeit bildet ein konzeptionelles Rahmenwerk, erstellt auf der Grundlage theoretisch-konzeptioneller Ansätze aus den Bereichen der Partizipationsforschung, Multi-Level Governance, und der Skalenliteratur. Dieses Rahmenwerk expliziert die Mechanismen, durch die partizipative und re-skalierte Formen von Governance potenziell zu einer effektiveren und legitimeren Umweltgovernance beitragen, unter besonderer Berücksichtigung relevanter Kontextbedingungen. Die empirische Anwendung dieses Rahmenwerks folgt einem Mixed-Methods Design, das qualitative, quantitative, mengentheoretische und Review-Methoden miteinander kombiniert mit dem Ziel zu möglichst validen Erkenntnissen zu gelangen. In einem ersten Schritt und mit Fokus auf die EU Wasserrahmenrichtlinie (WRRL) untersucht diese Arbeit dabei, ob und unter welchen Bedingungen Partizipation und skalare Umstrukturierung im europäischen Wasserregime tatsächlich stattfinden, um dann, in einem zweiten Schritt, zu untersuchen ob ein solcher Wandel von Governance auch zu umweltgerechten und legitimen politischen Entscheidungen und dem Aufbau sozialen Kapitals beiträgt. Die Forschungsergebnisse zeigen, dass Governancestrukturen sich bislang moderat veränderten, wobei sich bestehende institutionelle Strukturen und Erfahrungen als beständig erweisen. Dementsprechend und trotz neuerlicher Verschiebungen von Autorität auf alternative Akteure und Skalen, erfüllt der Staat weiterhin die Rolle der zentralen Autorität im europäischen Wasserregime. Dort, wo Partizipation und re-skalierte Governancestrukturen implementiert wurden, lässt sich ein positiver Zusammenhang mit der Effektivität und Legitimität umweltpolitischer Entscheidungen feststellen. Die Analyse stellt dabei das lineare Verhältnis zwischen politischen Inputs und Outputs in Frage und entwickelt stattdessen ein nuancierteres Bild, das Governanceprozesse als eine Komposition mehrerer, interdependenter Wirkungsmechanismen begreift, die, je nach spezifischer Ausprägung, zu verschiedenen Outcomes führen. Auf Basis eines derartigen, kontextspezifischen Verständnisses wird insbesondere das Spannungsverhältnis zwischen Legitimität und der Problemlösungskapazität politischer Outcomes entflochten, als beide als Resultat bestimmter, zusammenhängender Eigenschaften des Governancesystems und dessen Kontextbedingungen verstanden werden können.
Eine Analyse der Umsetzung und Leistungsfähigkeit von partizipativer, Multi-Level Governance im europäischen Wasserresourcenmanagement
Keywords: Environmental Governance; Water; European Union; Framework Directive; Ressourcenmanagement; Wasser; Europäische Union; Rahmenrichtlinie; 333.7 Natürliche Ressourcen, Energie und Umwelt